The effects of extreme low frequency pulsed electromagnetic field on bone mineral density and incidence of fractures in patients with end –stage renal disease on dialysis – three year follow up study - Rakočević-Hrnjak, Aleksandra; Vuksanović, Miljanka; Dimković, Nada; Djurović, Aleksandar; Petronijević, Nataša; Petronijević, Milan (Vojnosanitetski pregled, 2020)
Background/Aim. A variety of physical therapy options has been developed for the treatment of musculoskeletal disorders including those characterized with low bone mineral density (BMD). Extreme low frequency pulsed electromagnetic field (ELF-PEMF) can accelerate bone formation. Patients with end stage of renal disease (ESRD) are predisposed to high incidence of fractures due to bone disorder with multifactorial pathogenesis. Vitamin D, calcium supplements, antiresorptive and anabolic drugs in those patients have changed pharmacodynamics and pharmacokinetics and have minimal or limited effects. The aim of this study was to assess the effectiveness of long-term ELF-PEMF therapy applied in concordance with physical exercise on bone mass, incidence of new bone fractures and parathyroid hormone concentrations in ESRD patients on dialysis. Methods. In this 3-year prospective clinical trial, 151 patients with ESRD on dialysis program were subjected to treatment with ELF-PEMF (18 Hz, 2 mT) applied during 40 min after 10 consecutive dialysis procedures, 4 times through one year (120 treatments in total during three years) together with kinesitherapy (study group) or only with kinesitherapy (control group) on the voluntary basis. Results. Total of 124 patients have completed the study. In the study group (n = 54), regardless of sex, significant improvements of BMD, T-score and Z-score on both lumbar spine and femoral neck were achieved after 3-year treatment with ELF-PEMF. In the control group (n = 70), significant decreases of BMD, T-score and Z-score as well as the higher incidence of new bone fractures were recorded. Conclusion. ELF-PEMF could be a convenient and safe non-pharmacological therapeutic strategy for fracture prevention in nephrology practices.